Comparison of the Effectiveness of Mindfulness-Based Therapy and Transactional Analysis on Sexual Function and Sexual Satisfaction in Female Patients with Bipolar Disorder - Pidad, Fatemeh; Ghasemi Motlagh , Mehdi; Mafakheri, Abdollah (Applied Family Therapy Journal (AFTJ), 2025)
Objective: The aim of this study was to compare the effectiveness of mindfulness-based therapy and transactional analysis on sexual function and sexual satisfaction in female patients with bipolar disorder. Methods: In this study, 20 women with bipolar disorder who referred to the Gyrus Specialty Neurology and Psychiatry Clinic in Tehran from April to August 2022 were selected through purposive sampling and randomly assigned to three groups: mindfulness-based therapy, transactional analysis therapy, and a control group. All participants completed the Female Sexual Function Index (FSFI) by Rosen et al. (2000) and the Sexual Satisfaction Scale by Larson et al. (1998) before and after the intervention. The mindfulness-based therapy group underwent eight 90-to-120-minute sessions held twice a week, while the transactional analysis group received treatment in nine 60-to-120-minute sessions held twice a week. Data were analyzed using descriptive statistics and repeated measures analysis. Findings: The results indicated that both mindfulness-based therapy and transactional analysis therapy had an effect on sexual function and sexual satisfaction in female patients with bipolar disorder. Moreover, a comparison of the effectiveness of the two therapeutic approaches across all dimensions showed that mindfulness-based therapy had a greater impact on sexual function and sexual satisfaction in female patients with bipolar disorder compared to transactional analysis. Conclusion: Therefore, the use of mindfulness-based therapy is recommended in psychology clinics.